Are Liberal Arts Colleges Professional Schools? A Restudy. Topical Paper No. ll - Lepchenske, George L.; Harcleroad, Fred F.; Arizona Univ., Tucson. Office of Research and Study in Higher Education ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
This study sought to identify and describe changes in curriculum programs and instructional systems occurring among a selected sample of small, private liberal arts colleges between 1969-70 and 1974-75. This study supports the prediction, based on a 1957 study by E.J. McGrath and C.H. Russell, that a pattern of course work combining a broad, liberal education with some initial vocational competence would become the pattern in American liberal arts colleges. Criteria for this study were drawn from the previous study and data were collected from the same institutions. Findings indicated that professionally/vocationally-oriented programs increased at an accelerated rate between 1900 and 1974 and that significant changes were found in curriculum and instructional systems. Alternative instructional systems in the expanded curriculum encouraged the learning of practical applications for the liberal arts disciplines. Social and cultural demands for curriculum changes and educational services created a need for interinstitutional cooperation between small, private liberal arts colleges. Shared facilities and faculties expanded capabilities and helped alleviate financial pressures. Information on program offerings of the surveyed schools is appended. (SW)
Availability: Chairman, Committee on Higher Education, University of Arizona, 1415 North Fremont Avenue, Tucson, Arizona 85719 ($2.00).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Development; Career Education; College Role; Cooperative Planning; Curriculum Development; Educational Change; General Education; Institutional Cooperation; Institutional Research; Intercollegiate Cooperation; Liberal Arts; Private Colleges; Research Projects; School Surveys; Shared Facilities; Shared Services; Small Colleges; Undergraduate Study; Reports, Research